Nervous system and neurosecretory cells in cestoda Lytocestus vyasaei Pawar, 2011 (Caryophyllidea) - Pawar, Rajkumar T. (International Journal of Scientific Research in Biological Sciences, 2019)
The nervous system and neurosecretory cells of cestode Lytocestus vyasaei (Caryophyllidae) was investigated using histochemistry on the basis cytological structure. Morphologically the central nervous system consists of cephalic ganglionic mass and the lateral longitudinal nerve cords. The cephalic ganglionic mass consists of moderate number of apolar cells, unipolar cells, bipolar cells, and few multipolar cells, which are darkly stained. The bipolar cells are spindle shaped with two axons, unipolar cells are rounded with single axon and multipolar cells are with many axons with full neurosecretory material. The present findings suggest that and neurosecretory cells in nervous system may play an important integrative role of both neuronal and endocrine in the flatworm.